PENINGKATAN MEDIA BANTU TALI TERHADAP HASIL BELAJAR JALAN CEPAT PESERTA DIDIK SMPN 3 PONTIANAK - Maulana, Havid; Atiq, Ahmad; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the process of improving student learning in fast road use the media to help rope in students of grade VIII D of SMPN 3 Pontianak. whereas in this study using classroom action research (PTK), the research subject teachers collaborate with the students of class VIII D SMPN 3 Pontianak totaling 39 people. So the results of learning to walk fast through the medium of the auxiliary ropes in the first cycle can be improved then researchers continued in cycle II, the students complete as many as 39 students or 100% included in the category of completely. This Data shows that the research way fast through the medium of the auxiliary strap has been successfully performed because it has been more than KKM is 80%. Based on the results of research on the cycle I contained the results of the completeness with the number of 26 people with a percentage of 66.66% and students who have not completed a total of 13 people with the percentage of 33,34%. While disiklus II there was an increase in students which amounted to 39 people with a percentage of 100% and that is not yet completed does not exist.Â Â Keywords: Brisk Path, Learning Outcomes, Rope Media